Progression of articular and extraarticular damage in oligoarticular juvenile idiopathic arthritis - de Oliveira Sato, J. [UNESP]; Corrente, José Eduardo [UNESP]; Saad-Magalhaes, C. [UNESP] (Clinical & Exper Rheumatology, 2011)
Objective Evaluate damage in oligoarticular JIA, estimating its frequency, risks and probability over time.Methods A cross-sectional and retrospective analysis of Juvenile Arthritis Damage Index (JADI) scoring, with both articular and extraarticular components, active joint count, disability index by CHAQ and Steinbrocker class, physician's global assessment, child pain and overall well-being visual analogue scale (VAS), was conducted in patients with oligoarticular JIA. Damage risk factors were estimated by univariate analysis and by generalised linear model. The probability of damage over rime was estimated by survival analysis and damage progression rates were calculated by hazard function.Results Seventy-live JIA cases were assessed, 89.3% persistent and 10.7% extended oligoarthritis, with median follow-up duration 1.7.years (IQR 1.3-3.1). Damage occurred in 38.7%. JADI-A correlated moderately only with the number of limited joints (r(s)= 0.50, p < 0.0001). Female sex (OR 3.5, 95% CI 1.0-11.6), DMARD use (OR 3.9, 95%CI 1.0-15.0) and knee involvement (OR 4.2, 95%CI 1.3-13.5) were significantly associated with joint damage, whereas only joint steroid injection was associated with extraarticular damage (OR 5.9, 95% CI 1.8-1.9.3). Damage probability at 5 years was 50% for JADI-A. and 57% for JADI-E. Calculated hazard rates each year were 16.1% and 16.3%, for JADI-A and JADI-E, respectively.Conclusion Sex DMARD use and knee involvement were associated with joint damage, whereas only joint steroid injection was associated with extraarticular damage, which progressed at stable rates over ten years.
Keywords: damage; disability; juvenile idiopathic arthritis; oligoarthritis; outcome